Investigation on Electronically Coupled Distributed Generation Modeling and Control Strategies for Microgrid Applications - Bilal M. Eid; Nasrudin Abd. Rahim; Jeyraj Selvaraj; B. W. Williams (Current Topics on Mathematics and Computer Science Vol. 4, 2021)
For electronically coupled distributed generation, a single-stage power converter capable of both maximum power point tracking and unity power factor dispatching is presented. The best control parameters are found by modelling a solar array (the distributed generator) and a three-phase grid-connected inverter. To control parameters, the inverter’s controller employs inner and outer control loops. To dispatch at unity power factor, the inner control loop transforms input from the abc frame to the d, q, 0 frame. The new method, which can be applied in microgrid applications at the primary control level, tracks the maximum power point in the outer voltage control loop (local controller). A comparison of the active power provided by single-stage and two-stage power converters is shown, demonstrating that single-stage is more efficient. For the proposed single-stage converter system, a comparison is made between variable and fixed DC reference voltages in terms of active power yields. The effects of various ambient disturbances such as changing weather conditions, solar radiation with severe disturbances, and variable PV cell temperature on active and reactive power yields is investigated in this work. It is suggested that a dynamic reference voltage be used. Matlab/Simulink simulations validate its effectiveness under variable radiation and temperature conditions. Unity power factor operation shows that the single-stage power conversion system performs all tasks properly.